Peran Pemerintah Desa dalam Pelestarian Budaya di Desa Bagolo Kecamatan Kalipucang Kabupaten Pangandaran - Andini Andini; Asep Nurwanda; Regi Refian Garis (Pusat Riset dan Inovasi Nasional, 2025)
This research is motivated by the suboptimal role of the Village Government in preserving culture in Bagolo Village, Kalipucang District, Pangandaran Regency. The research method used is a descriptive method with a qualitative research approach. The data sources of this research are primary and secondary data. The primary data of this research is the result of interviews with 7 informants. The secondary data of this research are important documents relevant to the research. The data collection techniques of this research consist of observation, interviews and documentation. The data analysis of this research is data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of the Bagolo Village Government in preserving culture has not been optimal, as seen from five dimensions. 1). In the stabilizer dimension, cultural preservation planning is not optimal and there is minimal community involvement in the planning process. 2). In the innovator dimension, there is low technology-based innovation and limited resources to develop creative preservation methods. 3). In the modernizer dimension, there is a lack of use of modern technology for cultural promotion and documentation in order to attract the interest of the younger generation. 4). In the pioneer dimension, there is a lack of consistent community mobilization programs and arts groups to preserve culture. 5). In the implementation dimension, there are budget limitations, facilities and infrastructure, and lack of access to capital for artists. The results of this study indicate that efforts to preserve culture in Bagolo Village require strengthening collaboration between the village government and the community, optimizing the use of technology, adequate funding support, and planned and sustainable preservation strategies so that local culture remains sustainable amidst the flow of modernization.